Pengaruh Harga CPO Dan Nilai Tukar Rupiah Terhadap Harga Minyak Goreng Di Pasar Tradisional Kota Medan - Chairani, Zizah; Marliyah, Marliyah; Syarvina, Wahyu (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Palm oil is one of the most consumed and produced oils in the world. It is cheap, easy to produce and very stable for use in a wide variety of foods, cosmetics, hygiene products, and can also be used as a source of biofuel or biodiesel. Most palm oil is produced in Asia, Africa and South America because the oil palm tree requires warm temperatures, sunshine and lots of rainfall to maximize its production. This study aims to determine the effect of CPO prices and the rupiah exchange rate on cooking oil prices in traditional markets in Medan. The research method used in this research is a quantitative research approach with multiple linear regression data analysis methods with SPSS tools. The sample used is the time series January 2017- December 2021. The dependent variable used in this study is the price of cooking oil. While the independent variables (independent variables) used are CPO prices and the rupiah exchange rate. Based on the results of hypothesis testing on the t test, it is known that the significant value of CPO price is 0.000 (sig < 0.05) with a t count of 11.124 > 2.002 (t count > t table). The second hypothesis test showed that the rupiah exchange rate was significant at 0.181 (sig > 0.05) with a t count of 1.355 <2.002 (t count > t table). And based on the results of the third hypothesis test, it is known that the significant value is 0.000 (sig <0.05) with an F count of 63.543 greater than F table 3.16 (F count > F table). So it can be concluded that the two independent variables (CPO prices and the rupiah exchange rate) simultaneously have a significant effect on the cooking oil price variable.